TNF inhibitors appear to inhibit disease progression and improve outcome in Takayasu arteritis; an observational, population-based time trend study - Gudbrandsson, Birgir (Arthritis Res Ther, 2017)
BACKGROUND: Magnetic resonance imaging (MRI) and computed tomography (CT) angiography have now largely replaced interventional angiography in the diagnoses and follow up of Takayasu arteritis (TAK) but data on the effects of this change of imaging method on diagnostic delay and vascular damage, and detailed data on the effect of different treatment regimens on the accumulation of vascular damage are missing. The aim of this study was to assess time trends in diagnostic delay, therapeutic approaches, arterial lesion accrual, persistent disease activity and remission rates in TAK. METHODS: The study cohort included all 78 patients from the 1999 − 2012 population-based South-East Norway TAK cohort and 19 patients from a tertiary referral cohort. TAK was classified by the 1990 American College of Rheumatology criteria and/or the 1995 modified Ishikawa diagnostic criteria. Data were retrieved by review of electronic patient journals and imaging data analyses. RESULTS: Diagnostic delay fell significantly during the study period and the number of lesions at diagnoses fell from three to two. Patients diagnosed from 2000 onwards more often received up-front treatment with disease-modifying antirheumatic drugs (DMARDs) than those diagnosed before 2000 (51% vs 4%; p < 0.01), and they were more often treated with TNF inhibitors during the disease course (44% vs 14%). During the first 2 years after initiation of therapy, 10% (3/32) of TNF-inhibitor-treated patients developed new lesions, compared to 40% (16/40) on DMARD treatment (OR 0.13) and 92% (14/15) on prednisolone monotherapy (OR 0.02). Patients on TNF inhibitors had a higher sustained remission rate than patients on DMARDs (42% vs 20%; p = 0.03). From 2000 onwards, the proportion of patients without new arterial lesions during the first 5 years after diagnosis increased from 29% in the patients diagnosed in 2000–2004, to 39% in 2005–2009 and 59% of patients diagnosed in 2010–2012. CONCLUSION: Our observational data indicate that more aggressive use of TNF inhibitors and DMARDs improve the outcome in TAK, but damage accrual is a continuous challenge and sustained remission is still relatively rare. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-017-1316-y) contains supplementary material, which is available to authorized users.